MIKROTREMOR DAN PERCEPATAN TANAH MAKSIMUM KOTA MAKASSAR - Asdani Soehaimi (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Makassar city has a relatively far distance > 50 km to the seismic source zone,but the soft soil condition in this area produced significant amplification of earthquake ground shaking. Therefore, a microzonation study as a risk analysis of local site response is basicaly needed. In this research, the earhquake microzonation map was made based on a soil dinamic characterization of a microtremor investigation. The soil having a long predominant period is more risky compared to that having short period of soil. The dominant period of soil at this investigation was calculated based on horizontal towards vertical spectral ratios (H/V) of microtremors, meanwhile the microzonation map of Makassar City was made based on the variation of a predominant period. The result of calculation shows that the south-western part of Tamalanrea district has the longest predominant period. This predominant period gradually dereases to the eastern part of Makasasar City. Peak ground accelaration studies show the maximum ground accelaration is not defferent between one and the other districts. The maximun ground accelaration belongs to Biringkanaya,Tamalanrea and Manggala districts (58,80 gal, 56,84 gal and 55,86 gal for 500 years) in the eastern part of Makassar City. This ground accelaration value becomes less to the west, because the main seismic source zone of Walanae active fault is located at the eastern part of Makassar City.Â Keywords: microzonation, microtremor, earthquake source zone, site respons, peak ground acceleration